Institutional Analysis of Farmers’ Groups in the Management of Clove Farmland in North Toli-Toli District - Putri Anelia; Ratna Candra Sari (International Journal of Economic and Business Research, 2026)
This study examines the influence of farmer group institutional dimensions on clove agricultural land management in Tolitoli Utara District, Central Sulawesi. Employing a quantitative associative design, data were collected from 50 active clove farmers using purposive sampling, supported by questionnaires, interviews, and field observations. Multiple linear regression analysis was applied to evaluate the effects of organizational structure, member participation, formal and informal rules, and evaluation and supervision on land management practices. The results indicate that organizational structure and member participation have positive and significant effects, reflecting the importance of coordination and active engagement in improving agricultural performance. Conversely, formal and informal rules, as well as evaluation and supervision, exhibit significant negative effects when characterized by rigidity and administrative intensity, suggesting that excessive institutional control may hinder adaptability and reduce farmer initiative. Simultaneously, all variables significantly influence land management, with a high coefficient of determination indicating strong explanatory capacity. The findings highlight the need for adaptive and participatory institutional arrangements to enhance productivity and sustainability in smallholder clove farming systems.